2010
DOI: 10.1186/1471-2474-11-215
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-assessment of hallux valgus using the Manchester scale

Abstract: BackgroundHallux valgus (HV) is a common condition involving the progressive subluxation of the first metatarsophalangeal joint due to lateral deviation of the hallux and medial deviation of the first metatarsal. The objective of this study was to evaluate the re-test reliability and validity of self-assessment of HV using a simple clinical screening tool involving four standardised photographs (the Manchester scale), in order to determine whether this tool could be used for postal surveys of the condition.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 34 publications
1
42
0
4
Order By: Relevance
“…The 4-level Manchester scale has been shown to have good retest reliability (weighted κ = 0.78-0.90) 15 and a strong association with radiographic HV angle measurements (Spearman ρ = 0.73, P<.01). 17 Similarly, a 5-grade scale described by Roddy et al 23 has been shown to have very good observer repeatability (weighted κ = 0.82).…”
Section: Discussionmentioning
confidence: 99%
“…The 4-level Manchester scale has been shown to have good retest reliability (weighted κ = 0.78-0.90) 15 and a strong association with radiographic HV angle measurements (Spearman ρ = 0.73, P<.01). 17 Similarly, a 5-grade scale described by Roddy et al 23 has been shown to have very good observer repeatability (weighted κ = 0.82).…”
Section: Discussionmentioning
confidence: 99%
“…An excellent interexaminer repeatability (kappa coefficient κ = 0.86) was showed for this 4-point scale. [24] A high inter-rater reliability and validity of the HV angle between the photographic measurements and radiographs was demonstrated. Their ICC (>0.96) and Pearson correlation coefficient ( r  = 0.96) were excellent, and also their confidence interval (95% CI) limits of agreement were acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…Associated factors that were reported as categorical variables were collapsed into dichotomous categories for analysis. Subgroups of mild, moderate, and severe HV classified according to the Manchester Scale 33 were collapsed into the following dichotomous groupings: none/mild, or moderate/severe HV 34 . Additional data was requested from authors where means and SDs had not been provided in the original publication.…”
Section: Data Managementmentioning
confidence: 99%